Patient, Caregiver, and Decliner Perspectives on Whether to Enroll in Adaptive Deep Brain Stimulation Research - Outram, Simon; Muñoz, Katrina A.; Kostick-Quenet, Kristin; Sanchez, Clarissa E.; Kalwani, Lavina; Lavingia, Richa; Torgerson, Laura; Sierra-Mercado, Demetrio; Robinson, Jill O.; Pereira, Stacey; Koenig, Barbara A.; Starr, Philip A.; et al. (Frontiers in Neuroscience, 2021)
This research study provides patient and caregiver perspectives as to whether or not to undergo adaptive deep brain stimulation (aDBS) research. A total of 51 interviews were conducted in a multi-site study including patients undergoing aDBS and their respective caregivers along with persons declining aDBS. Reasons highlighted for undergoing aDBS included hopes for symptom alleviation, declining quality of life, desirability of being in research, and altruism. The primary reasons for not undergoing aDBS issues were practical rather than specific to aDBS technology, although some persons highlighted a desire to not be the first to trial the new technology. These themes are discussed in the context of ‘push’ factors wherein any form of surgical intervention is preferable to none and ‘pull’ factors wherein opportunities to contribute to science combine with hopes and/or expectations for the alleviation of symptoms. We highlight the significance of study design in decision making. aDBS is an innovative technology and not a completely new technology. Many participants expressed value in being part of research as an important consideration. We suggest that there are important implications when comparing patient perspectives versus theoretical perspectives on the choice for or against aDBS. Additionally, it will be important how we communicate with patients especially in reference to the complexity of study design. Ultimately this study reveals that there are benefits and potential risks when choosing a research study that involves implantation of a medical device.